Estrogen Suppresses Cytokines Release in cc4821 Neisseria meningitidis Infection via TLR4 and ERβ-p38-MAPK Pathway - Guo, Pengbo; Xu, Juan; Liang, Hao; Xu, Li; Gao, Wanying; Chen, Ziman; Gao, Yuan; Zhang, Maojun; Yu, Guangfu; Shao, Zhujun (Frontiers in Microbiology, 2022)
Estrogen has long been known to possess immune-modulatory effects in diseases, and multiple pathological conditions show great sex disparities. However, the impact of estrogen in Neisseria meningitidis infection has not been determined. The present study aimed to investigate the role of estrogen in N. meningitidis infection and the molecular mechanism. We selected thirty-five N. meningitidis isolates representing different clonal complexes (cc), serogroups, and isolation sources to infect the HBMEC cell line. Results showed that the expression of estrogen receptor (ER) β in N. meningitidis-infected cells was downregulated compared with that in normal cells. The expression of ERβ induced by invasive isolates was lower than that in carriers. Serogroup C isolates induced the lowest expression of ERβ compared with serogroup A and B isolates. We used four cc4821 N. meningitidis isolates to infect two kinds of host cells (human brain microvascular endothelial cells and meningeal epithelial cells). The results showed that 17 β-estradiol (E2) could inhibit the release of inflammatory factors interleukin (IL)-6, IL-8 and tumor necrosis factor-α after N. meningitidis infection via TLR4. E2 could inhibit the activation of the p38-MAPK signal pathway induced by N. meningitidis infection through binding to ERβ, and significantly inhibit the release of inflammatory factors in N. meningitidis-infected host cells. This study demonstrated that estrogen plays a protective role in N. meningitidis infection. ERβ is potentially associated with the release of inflammatory cytokines in N. meningitidis infection, which sheds light on a possible therapeutic strategy for the treatment of invasive diseases caused by N. meningitidis.